Cypriana Norwida słowo i druk - Nowak-Wolna, Krystyna (Stylistyka, 2021)
In the article The Word and Press of Cyprian Norwid the following questions ave iscus- sed: the opinions of Cyprian Norwid on the art of reading aloud and declamation, the views of Wojciech Siemion on the method of deciphering and vocal interpretation of Nor- wid’s poetry, recitations of the poem Bema pamięci żałobny-rapsod/ A Funeral Rhapsody in Memory of General Bem by Irena Jun and Zbigniew Zapasiewicz as well as the rendi- tion by Czesław Niemen. Cyprian Norwid (one of the most prominent representatives of Polish Romanticism) perceived declamation as a complement to the art of reading. For the poet a complement is not a simple act of filiing in the missing part, but a fulfillment of an idea, an approxima- tion to an ideał. Ali the literary works of Norwid, not only dramas, constitute a perfect score for a reciter. They boast numerous emphases, variously marked pauses, ties, com- mas and interjections.The poem Bema pamięci żałobny-rapsod/ A Funeral Rhapsody in Memory of General Bem was created in 1851 on the first anniversary of the death of General Józef Bem and presents a poetic picture of the funeral of a hero of Poles and Hungarians. The description of the funeral reters to the Ancient and the old Polish pattems. The masterpiece Bema pamięci żałobny-rapsod/A Funeral Rhapsody in Memory of General Bem is a hexameter.Wojciech Siemion, a brilliant Polish actor and an excellent reciter of Norwid’s poetry, proposes an interesting interpretation of the masterpiece. First of all, sińce Bema pamięci żałobny-rapsod/ A Funeral Rhapsody in Memory of General Bem is a funeral march, it should be read slowly, with the rhythmic feet marked, conforming to the rhythm of a funeral march. Secondly, in order to render the rhythmic structure of the poem transaccen- tuations should be used.In his performance another eminent actor and reciter, Zbigniew Zapasiewicz, prese- rves in most cases the rhythm of the poem. In the discussed recitation three unfolding rhythmic structures can be distinguished: slow, stately and powerful steps of the marching knights tum into a funeral march, and both rhythms intermingle with an interrupted “private” phrase when the performer reveals his own feelings.In comparison with Zapasiewicz’s recitation, the performance of Irena Jun (also an es- teemed actress and an excellent reciter of poetry) displays a bigger emotionality load, morę individual ideas which, however, do not substantially alter the ideological signifi- cance of the literary original. Using multifarious vocal means the reciter shows the musical layer of the masterpiece.Czesław Niemen, a singer, realises in his performance the rhythmic scheme inscribed into the poem by Norwid. And in doing so he is morę consistent than the reciters. The performance is very emotional as a result of the value of the musie itself, which - as it should be emphasized - does not drown out the poem’s words, but it accentuates them. Diverse, changeable, subtle shades of the singer’s timbre have significance as well.Keywords: recitation, declamation, a living word, rhapsody, reciters work, recitation work, rhythm, rhyme, musie, poem, poetry, song, rhythmic foot, accent, syllable, caesura, clause, intonation, intoneme, phrase, pause, silence, cadence, anti-cadence, half anti-ca- dence, progredience, hexameter, phonetic instrumentation, strophe.